Botox: Buy Me Beauty! - Hurkadle, Jyothi Kiran; Jatania, Archana; Shanthraj, Ravi; Lakshmi, Bhagya; Subbiah, Pradeep; Linga, Shiva (Journal of Orofacial Research, 2012)
‘Beauty lies in the eyes of the beholder’. Beauty has been admired since time immemorial not only by the medical personals but also by the general masses. Beauty undoubtedly has a strong influence on human life. Orthodontists have a special interest in facial beauty. One of the most socially significant of human behaviors is expression of emotions on the face with smile being the most important of those emotions. The display of excessive gingival tissue in the maxilla upon smiling has been called a ‘gummy smile’, a condition some consider esthetically displeasing. Some people with excessive gingival display are self-conscious or embarrassed about it, and some are psychologically affected. There are a number of different treatment methods described in the literature for the treatment of gummy smile. These includes both surgical and nonsurgical options, including Le Fort I osteotomy, crown lengthening procedure, maxillary incisor intrusion, self-curing silicone implant injected at the anterior nasal spine and finally myectomy and partial resection of the levator labii superioris or muscle repositioning. Some patients do not wish to go through the long presurgical orthodontic treatment in preparation for a Le Fort I osteotomy while others wish to avoid the possible complications surrounding surgery, such as postoperative pain, swelling and infection, permanent or temporary nerve damage and root damage during osteotomy. A nonsurgical alternative for reducing excessive gingival display caused by muscle hyperfunction would be advantageous. Botulinum toxin has been under clinical investigation since the late 1970s for the treatment of several conditions associated with excessive muscle contraction or pain. The aim of this article is to give an overview about the science of Botox and its various uses.